Modern languages in the primary school - Hood, Philip, 1951-; Tobutt, Kristina; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2009)
In this practical text, the authors look at how foreign language learning can be integrated into the primary classroom. They offer ideas on how to start language programmes in schools, or enhance those which are already in place.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Language and languages -- Study and teaching (Elementary); Electronic books